The Influence of Institutional Goals, Participation, and Lecturer Commitment on Lecturers’ Performance University of Riau - Yundri Akhyar; Martinis Yamin; Abdul Halim (PT. Anagata Sembagi Education, 2026)
This study aims to analyze the influence of institutional goals, participation, and lecturer commitment on lecturer performance at the University of Riau. The research employed a quantitative correlational design. The population consisted of 1,464 permanent lecturers registered in SINTA, from which a sample of 147 was selected using proportional stratified random sampling. Data were collected through a five-point Likert scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using multiple regression and mediation testing with the bootstrap method to examine both direct and indirect effects. The results revealed that institutional goals, participation, and lecturer commitment have positive and significant effects on lecturer performance, with an adjusted R² value of 0.63, indicating that these three variables explain 63% of the variance in lecturer performance. Lecturer commitment showed the most dominant effect and partially mediated the relationship between institutional goals and lecturer performance. These findings indicate that lecturer performance is determined not only by structural factors such as institutional goal clarity but also by psychological factors such as engagement and commitment. The study implies that strengthening institutional communication, encouraging lecturer participation in decision-making, and developing professional commitment are essential strategies to achieve sustainable academic excellence.